Assessment of prescription pattern and prescription error in outpatient Department at Tertiary Care District Hospital, Central Nepal - Rajeev Shrestha; Srijana Prajapati (Taylor & Francis Group, 2019)
Background The rational use of medicine improves patient's quality of life. Excessive and inappropriate prescriptions result in severe consequences. The study of drug use patterns and prescription errors is necessary to promote rational drug use in developing countries. The aim of the study was to evaluate prescription practice and help to the quality use of medicine. Methods A retrospective, cross-sectional and quantitative study was conducted at Bharatpur District Hospital in central Nepal. The outpatient prescriptions retained at the pharmacy from November to December 2017 were used to evaluate prescription patterns and errors. The total of 770 prescriptions were reviewed. The stratified random sampling method was used. Result The total of 2448 drugs were prescribed in 770 prescriptions or patients. The average number of drugs per encounter was 3.2. The percentage of encounter with antibiotic and injection was 37.9% (n = 292) and 0.7% (n = 5), respectively. The percentage of drugs prescribed by generic and from an essential medicine list of Nepal was 2.9% (n = 72) and 21.3% (n = 521), respectively. The most common 32.5% of prescriptions contain three drugs and 24.7% of prescriptions contain four drugs. The average prescription errors per prescription were 3.4. Among total errors, omission errors related to prescriber were 1.5 (n = 1135), omission errors related to the drug were 1.5 (n = 1189) and commission errors were 0.3 (n = 269). The total of 249 drug interactions were found in 19.1% (n = 147) prescriptions. The common prescription errors were due to failure to mention prescriber name 87.5% (n = 674), failure to mention prescriber signature 19.2% (n = 148) and failure to mention diagnosis 39.2% (n = 302). Conclusion The study shows low compliance with WHO prescribing indicators and high prescription errors. The prescribing practices were not confirmed to the standard recommended by WHO. Prescribing from the Essential Drug List (EDL), low rates of generic prescribing, high antibiotic prescribing and polypharmacy were a major problem. The study found major errors in prescriber and prescribed medicine details. Remarkable drug interactions were seen in prescribed medicines. The study recommended necessary practices and policy formulation and implementation by DTC and regulatory bodies to promote the rational use of medicine.